Histological and Ultrastructural Studies on Bursa of Fabricius of Kadaknath Breed of Poultry - Yadav, Maneesh Kumar (Indian Journal of Veterinary Anatomy, 2020)
The study was conducted on bursa of Fabricius of twenty five Kadaknath birds from day old to thirty weeks of age. Bursa of Fabricius was composed of four tunics as tunica mucosa, tunica submucosa, tunica muscularis and tunica serosa. The mucosa was lined by pseudostratified columnar epithelium except at crypts where it was simple columnar epithelium. Ultrastructurally, granules were present in apical portion of principle cells of epithelium. Epithelium had four types of cells as type-I, type-II, type-III and type-IV. The numbers of and beneath the epithelium of bursa of Fabricius which was unique characteristic in present study. In cortex and edulla of follicle small, medium and large lymphocytes were found along with plasma cells, macrophages, granulocytes and fibrocytes. On the basis of ultrastructure, there were three types of reticuloepithelial cells were found in follicles.